DOCUMENTATION IN ACCOUNTING LITERATURE. - Winakon, Arthur H.; Borth, Daniel (The Accounting Review, 1934)
Abstract Publishers of books are frequently prone to look upon footnotes as added and unnecessary expense. But this can be no more true of books in the field of accounting than in the many other fields of thought. Furthermore, it may be stated that no writer would permit a publisher to delete from his treatise those thoughts which he felt were essential thereto; by the same argument he should refuse to permit the publisher to omit footnotes and references if they are material to his contribution. Publications in other fields have survived the desires of publishers to economize; accounting can do the same if writers see the merit of references and insist on them. In the long run, and for its own best welfare, accounting cannot be judged in the light of its limiting circumstances such as enumerated above. It must be judged in the light of its true possible social value and its position relative to other sciences. If accounting writers are not prepared to uphold the standards ordinarily exacted in other fields, it is accounting that must suffer by comparison.